Obesity and its co morbidities in children and adolescents - AL-Jaff, Bushra A. (AL-Kindy College Medical Journal, 2016)
Background: Obesity has become one of the most important public heath problems all over the world.An epidemic of obesity is affecting children and adolescents across the developed and developing countries in recent years. As the prevalence of obesity increased, so did the prevalence of co morbidities like metabolic and endocrine diseases.Objectives: To overview obesity clinical features and the prevalence of associated co morbidities in children and adolescents attended the obesity researches and therapy center in Alkindy medical collage.Type of study: This is a cohort observational studyMethods : Obese child and adolescents aged 4-15year attended the obesity research and therapy unit in AL Kindy medical collage from the 1st of September to the 31st of October 2015, Results: Children and adolescents are equally susceptible to obesity but Girls are twice susceptible to have obesity than boys 34:16 (68%: 32%). The study shows that all patients have BMI>95th and 84% of them have BMI >99th percentile. Only 26% of patients have height more than 95th percentile. More than 2/3 of patients have snoring and other sleep disorders, most of them are adolescent boys. 22% are hypertensive mainly adolescents.42% have hyperglycemia,40% hypercholestremia, and 70% have high triglyceride level with no gender or age group association. Increased appetite (88%), family history of obesity(82%) and sedentary life style (76%) are the most common causes of children and adolescents obesity. Conclusion: Novel approaches in the prevention and treatment of childhood and adolescent obesity are urgently required particularly to family behavior pattern. Key words: Obesity, childhood, adolescent.